Chemostratigraphy and Paleoenvironment of the Miocene Organic Rich Sediments in the East Kutai Sub-Basin, Indonesia - Asep Kurnia Permana; Aris Kusworo; Joko Wahyudiono; Y A. Sendjaja; Hermes Panggabean; L Fauziely (Jurnal Geologi dan Sumberdaya Mineral, 2022)
The Miocene sedimentary rocks in Samarinda area constrains organic rich sediments, which are considered as a good source rocks hydrocarbon in the East Kutai Sub-Basin, Kalimantan. The high organic material content within the sediments is related to the dynamics of depositional environment in deltaic setting. The accumulation and characteristics of organic matter in this area may be influenced by multiple factors, under a complex physical-chemical processes. Geochemical data of major and trace elements obtained for a total 309 outcrop samples from four locations were interpreted to define chemostratigraphic and paleoenvironmental conditions (paleoproductivity, detrital influx, paleoredox and paleosalinity) responsible for organic carbon accumulation and source rocks characterization. Stratigraphic variation in inorganic geochemistry allows two chemostratigraphic packages to be defined and correlated within the Miocene sedimentary sequences. These chemostratigraphic packages are geochemically differentiated using SiO2/Al2O3, TiO2/Al2O3, Na2O/Al2O3, TiO2/Nb and Sr/Ba ratio values. The chemical alteration index (CIA) suggests that the sedimentary unit was deposited in a hot and humid climate, with moderate to intensive weathering intensity. Detrital material input proxies (Si/Al, Ti/Al) indicate that the low Si/Al and Ti/Al ratios reflect a low material input providing an increasing organic matter accumulation in the Middle Miocene. However, paleoproductivity proxies (P/Ti, Ba/Al) show the organic matter enrichment is not restrained by water column productivity, as indicated by a weak correlation between TOC and productivity index. In addition, paleosalinity index (Sr/Ba) and redox indicators (V/Cr, V/Sc U/Th and Mo/Al) indicate that the sediments were deposited in a brackish environment with dysoxic to suboxic conditions and might be the main control in the enrichment of organic matter in the study area. Thus, the detrital material influx and paleoredox conditions controlled organic accumulation and source characteristics the Miocene sedimentary sequence of the Kutai Basin.Keywords: Chemostratigraphy, Kutai Basin, paleoenvironment, source rocks.